2005
DOI: 10.1002/syn.20156
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a 5-HT1A receptor agonist on striatal dopamine release

Abstract: 5-HT1A receptor agonists consistently reduce neuroleptic induced catalepsy in rats. A serotonin-dopamine interaction has been proposed to underlie this effect. Specifically, 5-HT1A receptor agonists may reduce the activity of serotonergic projections that inhibit dopaminergic nigrostriatal neurones, therefore increasing dorsal striatal dopamine levels and partially overcoming the neuroleptic blockade of D2 receptors. We tested the hypothesis that 5-HT1A receptor agonists increase striatal dopamine release in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 64 publications
0
16
0
1
Order By: Relevance
“…The results of the present study are also consistent with an earlier demonstration of the chronic effects of oral citalopram (Tiihonen et al, 1996). Other human studies using such agents as the selective 5-HT1A receptor agonist, flesinoxan or single oral doses of the anti-depressants nefazodone or paroxetine did not report significant alterations in striatal [ 11 C]-raclopride receptor availability (Bantick et al, 2005; Fowler et al, 1999). Although the results of some human [ 11 C]-raclopride studies suggest that pharmacologic-induced increase in serotonin produces a secondary increase in dopamine concentrations, these findings are in contrast to previous PET studies in anesthetized nonhuman primates that show an inhibitory role of serotonin with respect to striatal dopamine (Dewey et al, 1995).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of the present study are also consistent with an earlier demonstration of the chronic effects of oral citalopram (Tiihonen et al, 1996). Other human studies using such agents as the selective 5-HT1A receptor agonist, flesinoxan or single oral doses of the anti-depressants nefazodone or paroxetine did not report significant alterations in striatal [ 11 C]-raclopride receptor availability (Bantick et al, 2005; Fowler et al, 1999). Although the results of some human [ 11 C]-raclopride studies suggest that pharmacologic-induced increase in serotonin produces a secondary increase in dopamine concentrations, these findings are in contrast to previous PET studies in anesthetized nonhuman primates that show an inhibitory role of serotonin with respect to striatal dopamine (Dewey et al, 1995).…”
Section: Discussionmentioning
confidence: 94%
“…Serotonin modulation of dopamine function is relevant to several neuropsychiatric conditions including schizophrenia, obsessive compulsive disorder, major depression and drug abuse and thus, has been a particular focus of [ 11 C]-raclopride studies in nonhuman primates and humans (Bantick et al, 2005; Rosa-Neto et al, 2004; Smith et al, 1997; Vollenweider et al, 1999). Several human studies have observed that a pharmacologic increase in serotonin concentrations produced a reduction in striatal D2 receptor availability (Smith et al, 1997; Tiihonen et al, 1996; Vollenweider et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies using positron emission tomography reported the involvement of the 5-HT 1A receptor in dopaminergic cell activity in caudate, putamen and mesolimbic pathway (Bantick et al 2005), and 5-HT 2 receptors seem to increase the tonic release of DA in the nucleus accumbens and mesolimbic pathway, through an interaction with GABA (Devaud and Hollingsworth 1991;Parsons et al 1999). >Both 5-HT 1A and 5-HT 1B receptors have been implicated in exerting stimulatory effects on mesocortical and prefrontal DA release (Hagino and Watanabe 2002;Morrow et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…As mentioned above, some of the atypical antipsychotics are 5-HT1A receptor partial agonists, and this property had been shown to enhance their clinical efficacy. They act by enhancing dopamine release which plays a major role in the antidepressant and anxiolytic effects seen upon postsynaptic activation of the 5-HT1A receptor 18 . Moreover, 5-HT1A receptor antagonists such as lecozotan have been shown to facilitate certain types of learning and memory in rodents by stimulating the release of glutamate and acetylcholine in various areas of the brain 19 .…”
Section: Introductionmentioning
confidence: 99%